Peranan LKM-A dalam Mendorong Percepatan Adopsi Teknologi Jagung di Sumatera Barat - Nasrul Hosen (Politeknik Negeri Lampung., 2014)
Microfinance Institutions (LKM-A) is a venture capital under the auspices gapoktan. LKM-A growing and evolving through the Rural Agribusiness Development Program (PUAP) with facilitation fund capital gain Rp. 100 million per gapoktan which began in 2008 and continued until 2013. LKM-A were grown in 2008 and 2009 has been developed with venture capital indicators (asset) is over Rp. 150 million. The capital rent to farmers to develop agricultural businesses, one of which corn business. This paper aims to study the expression of the results to identify maize technology adoption rates in the region work Gapoktan/LKM-A in the maize production centers like Limapuluh Kota and Tanah Datar district. Survey conducted in 2012 by taking a sample of 2 Gapoktan per district with LKM-A asset criteria over Rp. 150 million and has been operating 3-4 years. Sample farmers in each region gapoktan 30 people selected randomly, consisting of 15 farmers member of LKM-A and 15 farmers not a member of LKM-A. The data were analyzed by farm analysis and comperative analysis before and after the LKM-A. The result showed that after the LKM-A, maize technology adoption by farmers of members increased compared to before there LKM-A. Before there LKM-A. majority of farmers in Limapuluh Kota District has adopted several major technologies such as (i) seed labeled 70%, (ii) 90.0% of hybrid, (iii) site-specific fertilization 36.7%. Once there LKM-A. turns the main technology adoption increases, respectively, to 100.0%, 100.0% and 90.0%. Adoption of maize technology before there LKM-A. in Tanah Datar, namely (i) the user seed labeled 63.3%, (ii) hybrid 73.3% and (iii) site-specific fertilization 30.0%, and after LKM-A. increased adoption row to be 90.0%, 90.0% and 70.0%. Other technology components also changed for the better. Technology adoption by members LKM-A is also more than the farmers are not members at the same time. Technology improvements to increase corn yields and farm profits and additional economically viable investment for technological improvements by indicators in Limapuluh Kota district MBCR = 2.72 and 1.76 in Tanah Datar district. Conclusion, that the dissemination of the technology needs to be followed by the provision of capital resources in conditions of available technology, is able to accelerate the adoption of technology. Suggested to the stakeholders that are easily accessible sources of capital such as small farmers LKM-A. needs to be developed in rural areas, in order to support the acceleration of adoption of technological innovations and development of agribusiness at farmer level.. Keywords: Corn, LKM-A, capital, technology adoption, income